2020
DOI: 10.1109/access.2020.2970205
|View full text |Cite
|
Sign up to set email alerts
|

A General Fast Power Flow Algorithm for Transmission and Distribution Networks

Abstract: Fast power flow calculation is generally required in static security analysis and power system optimal planning. And the classical DC power flow algorithm, due to its simple mathematical model, linearized equation, and rapid solving speed, is widely utilized. However, the classical DC power flow algorithm has been found to be only suitable for high voltage transmission networks with small branch impedance ratio. To address this issue, a general fast power flow algorithm is proposed. Utilizing this method, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Posteriorly, some authors focused on the inefficiency problems caused by Jacobian calculation in Newton-based solvers thus applying sparsity routines [10] and decoupled techniques [11], [12]. Since then, many advances have been made in the PF calculation from different perspectives, developing linear models [13]- [15], applying or developing high order Newton-like methods to the PF analysis [16], [17] or deriving alternative formulations [18]- [20].…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Posteriorly, some authors focused on the inefficiency problems caused by Jacobian calculation in Newton-based solvers thus applying sparsity routines [10] and decoupled techniques [11], [12]. Since then, many advances have been made in the PF calculation from different perspectives, developing linear models [13]- [15], applying or developing high order Newton-like methods to the PF analysis [16], [17] or deriving alternative formulations [18]- [20].…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Step 5: The fitness of each search agent is computed according to (5). If any search agent does not satisfy any constraints, then that infeasible search agent is penalized as discussed in Section 2.…”
Section: Lf Using Qohbo Techniquementioning
confidence: 99%
“…Further, the problem variables are updated by utilizing power mismatches and the Jacobian matrix [1]. In [5], a fast load flow algorithm was suggested to solve both the transmission and distribution networks by considering a high impedance ratio of the systems. Similar to [5], the authors in [6] demonstrated a methodology that combined the fast decoupled load flow technique and complex per unit normalization method to deal with both transmission and distribution systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of voltage offset has also been identified in other linearized power flow, e.g. [44] where non-integral offset correction technique that is rather computationally intensive (for real-time dispatch problems), is proposed. To incorporate the proposed corrective term into the optimal control, ( 11), ( 14) and ( 17) shall be modified to:…”
Section: Integral-based Corrective Termmentioning
confidence: 99%